2008
DOI: 10.1016/j.jmb.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Organisation and Role of Myosin Binding Protein C in Normal Striated Muscle by Comparison with MyBP-C Knockout Cardiac Muscle

Abstract: Myosin binding protein C (MyBP-C) is a component of the thick filament of striated muscle. The importance of this protein is revealed by recent evidence that mutations in the cardiac gene are a major cause of familial hypertrophic cardiomyopathy. Here we investigate the distribution of MyBP-C in the A-bands of cardiac and skeletal muscles and compare this to the A-band structure in cardiac muscle of MyBP-C-deficient mice. We have used a novel averaging technique to obtain the axial density distribution of A-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
163
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(182 citation statements)
references
References 34 publications
18
163
1
Order By: Relevance
“…However, considering the range of sarcomere lengths studied here (SL ϭ 1.9 -2.3 m), the lengths of the cardiac thick and thin filaments (48,49) and the structure of the cardiac C-zone (48), full overlap is predicted between cMyBP-C and the cardiac thin filament at both the short and long SL. Hence, in the heart a mere change in position between cMyBP-C and the cardiac thin filament is unlikely to underlie LDA or its modulation by PKA.…”
Section: Discussionmentioning
confidence: 95%
“…However, considering the range of sarcomere lengths studied here (SL ϭ 1.9 -2.3 m), the lengths of the cardiac thick and thin filaments (48,49) and the structure of the cardiac C-zone (48), full overlap is predicted between cMyBP-C and the cardiac thin filament at both the short and long SL. Hence, in the heart a mere change in position between cMyBP-C and the cardiac thin filament is unlikely to underlie LDA or its modulation by PKA.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence has previously been presented that cardiac MyBPC-3 together with actin, titin, myomesin, and other sarcomeric partners forms cytoskeletal links guiding thick filament assembly in cardiomyocytes (Van Der Ven et al, 1999;Bhuiyan et al, 2012) and that this process is affected in MyBPC-associated cardiomyopathy (Freiburg and Gautel, 1996). In the cardiac muscle, ablation of MyBPC-3 does not alter the A-band length (Luther et al, 2008), suggesting that removal of this isoform alone does not affect thick filament length in vivo. The slow skeletal MyBPC-1 has been shown to regulate the thick filament assembly via interactions with obscurin (Ackermann et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…MyBPC is located in the C-zone of the sarcomere at a periodicity of 43 nm (Rome et al, 1973;Luther et al, 2008) with close interactions with other proteins. It has been shown that the cardiac MyBPC in the sarcomere affects cross-bridge force production; the cross-bridges in the C-zone (with MyBPC) generate higher active force (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three distinct isoforms of MyBP-C, i.e., fast skeletal, slow skeletal, and cardiac. The localization of cMyBP-C to discrete transverse stripes in each half of the A band (13) (Fig. 1A) is characteristic of the protein in all types of vertebrate striated muscle, and the regularity of its distribution led to the initial suggestion that MyBP-C is a structural protein.…”
Section: Localization Of Cmybp-c In the Cardiac Sarcomerementioning
confidence: 99%